Upaya Pembuktian dalam Menerapkan Pidana Denda Bagi Pelaku Tindak Pidana Narkotika - Hidayat, Zulfian; Ismansyah, Ismansyah; Rias, A. Irzal (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
In Law Number 35 of 2009 concerning Narcotics, the threat of criminal fines has significant punishment characteristics, with the amount of fines ranging from one hundred million rupiah to twenty billion rupiah. However, Article 148 of the Narcotics Law only stipulates a maximum imprisonment of 2 (two) years as a substitute for a fine, so there is a normative difference between the amount of the threat of criminal fines and the provisions of criminal penalties in lieu of fines. This certainly does not meet the judge's considerations in imposing criminal fines and efforts to prove the application of criminal fines for perpetrators of narcotics abuse. This research is an empirical, descriptive juridical research using primary data obtained by interviewing the Panel of Judges at the Payakumbuh District Court and using secondary data obtained from library studies of various legal literature and then analyzed qualitatively. The results of this study The judge's consideration in imposing sanctions tends to be more on imprisonment than fines because there is an imbalance between the amount of the fine threatened with a relatively light substitute prison sentence. The perpetrator's economic factors and the low substitute prison sentence (maximum 2 years) cause convicts to prefer serving a prison sentence rather than paying a fine.